Učinkovitost kolektivnega varstva delavskih pravic digitalnih nomadov - Ušen, Jana (Pravni letopis, 2025)
The paper examines the determination of jurisdiction and applicable law in representative action proceedings aimed at the protection of the labour rights of digital nomads. Their crossborder mobility and non-territorial nature of work, combined with the collective enforcement of claims, create challenges in the application of the Brussels I bis and Rome II Regulations. Based on the analysis of the Court of Justice of the European Union’s case law and doctrinal sources, the article finds that the existing rules of European private international law do not provide digital nomads with effective collective legal protection, leaving them isolated in the pursuit of their rights.
Keywords: applicable law; digital nomads; digitalni nomadi; European private international law; evropsko mednarodno zasebno pravo; international jurisdiction; mednarodna pristojnost; Mednarodno zasebno pravo; merodajno pravo; Pravice delavcev; representative action; zastopniška tožba